Teachers' Roles in Character Education through Pancasila Education: A Qualitative Study of Fourth-Grade Students - Friscilia Friscilia; Lista Lista; Kenny Lorensa; Salwa Nabila; Fitti Guahira; Juwita Crestiani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study aims to describe the role of teachers in implementing character education for fourth-grade students through Pancasila Education learning at SDN 5 Salamae. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of fourth-grade teachers and fourth-grade students at SDN 5 Salamae. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation and technique triangulation. The results of the study indicate that teachers play a guiding role in implementing character education through Pancasila Education. This implementation is carried out by fostering habits, setting an example, providing motivation and guidance, and reinforcing students' positive behaviors. The character values cultivated include discipline, religiosity, patriotism, and responsibility. Discipline is instilled by encouraging habits such as punctuality, adherence to rules, and the timely submission of assignments. Religiosity is fostered through practices such as prayer, exchanging greetings, and respecting diverse beliefs. Patriotism is developed by introducing Indonesia's cultural diversity and instilling a sense of national pride. Meanwhile, responsibility is cultivated by encouraging students to complete their tasks and fulfill their obligations. The findings indicate that the implementation of character education through Pancasila Education was perceived to contribute positively to shaping students' character. This success is supported by the teachers' consistency in setting examples, fostering habits, and providing guidance throughout the learning process.